課程變革的趨勢和具澳門特色的課程發展 - Ge, Rochelle Yun (2023)

澳門特殊與融合教育的發展及教師培訓 - Ge, Rochelle Yun (2023)

在教育中促進無偏見和可靠的人工智能:賦能學生認知能力 [Presentation] - Wu, H. (2023)

Understanding Chinese Model of Government-University-Industry Collaborations in Research and Education: The Case of Macau SAR. - Ge, Yun (2023)
Higher Education in Macau has been benefiting from a multi-layered institutional environment under China’s One-Country-Two-Systems. This presentation introduces research and education policies and practices of Macau universities under China’s national plan of the Greater Bay Area development. It aims to demonstrate and analyze how higher education actors collaborate with local and regional governments and industrial sectors in human capital formation and research innovations.

Tracing Modern Macau’s Evolving Global Role Views from Transnational Archives - Roberts, Priscilla (2023)

SOUNDSCAPE.AI - A Sonic Perspectives on Macau - Estadieu, G (2023)

Reciprocity in a school-university partnership project: Towards a Macau-based Give-Get Model - Chu, K. W.; Mak, M. C. K.; Ng, M. H.; Wong, U. W. K.; Cheng, P. W.; Tse, T. P. M.; Ho, G. W. S (2023)

Macau's First Modern University: Exploring the Early History of the University of East Asia - Roberts, Priscilla (2023)

Intelligent Data Fusion System for Assessing and Classifying the Long-Term Effects of Exposure to COVID-19 in Pregnancy (Long Covid): Associated Neurophysiological and Epigenetic Mechanisms and Consequences for Infant Development - Lobo Marques, J. A. (2023)

Impacts of Policies and Infrastructure on the Usage of Electric Vehicles in Macao - Weng Chi Lei; Tai, On Teng (2023)
Publisher: Unpublished

From ‘Mixed Methods’ to ‘Integration’ in Social Science Research - Morrison, Keith (2023)

Fr. Yves Raguin, S.J. and Interreligious Dialogue - Duraj, Jaroslaw (2023)

Do students in different courses of study think the same way in complex problem solving? [Poster presentation] - Wu, H.; Molnár, G. (2023)

Developing programs for preschool children to enhance Chinese literacy: A Macau-based example. - Chu, K. W.; Mak, M. C. K.; Tse, T. P. M.; Cheng, P. W.; Ho, G. W. S; Ng, M. H. (2023)

Developing programs for preschool children to enhance Chinese literacy: A Macau-based example - Chu, K. W.; Mak, M. C. K; Tse, T. P. M.; Cheng, P. W.; Ho, G. W. S.; Ng, M. H.; Ng, S. K. (2023)

Connecting Neuromarketing and AI - a path to new insights and analysis - Marques, J. A. L. (2023)

AI-based Multimodal Qualitative Mapping of Macao Soundscape - Estadieu, G; Cheung, Y.Y. (2023)